Efektivitas Teori Belajar Berbasis Pendidikan Inklusi untuk Siswa Berkebutuhan Khusus di Madrasah Ibtidaiyah - Najwa Ramadhani Nasution; Abdul Wahab; Riska Nasution (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
Inclusive education at Madrasah Ibtidaiyah (MI) seeks to ensure equitable learning opportunities for all students, including those with special educational needs. This paper explores how the implementation of various learning theories functions within inclusive education settings in madrasahs. Based on a review of existing literature and secondary data analysis, it is evident that employing theories such as behaviorism, cognitivism, and constructivism can enhance both the engagement and academic performance of students with disabilities. Nonetheless, the effectiveness of these approaches is closely tied to several factors, including teacher qualifications, the availability of supportive infrastructure, and the involvement of parents. To fully realize the goals of inclusive education in MI, learning strategies must be both adaptable and collaborative in nature.